A first workbook of Russian - Richards, I. A. (Ivor Armstrong), 1893-1979; Jasiulko, Evelyn; Gibson, Christine (New York : Washington Square Press, 1963)
This book is designed to teach beginners (or those whose knowledge has become misty) how to write in Russian. It is called a WORKBOOK because it is intended primarily for use with the basic textbook RUSSIAN THROUGH PICTURES, BOOK I. Specifically, this WORKBOOK will help the learner exercise and check the knowledge of Russian covered in the first half of RUSSIAN THROUGH PICTURES, BOOK I, whether that knowledge has been acquired from a study of the parent text or from some other source.
'For use with Russian through pictures, book 1.'
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Russian language -- Study and teaching